Implementing Content and Language Integrated Learning to Improve 11th Graders English Comprehension (2019)
ABSTRACT: This action research project was developed in order to analyze the implications of implementing content language and integrated learning in a public school in Medellin, Colombia and how it improves English comprehension. This project was carried out at the CEFA in an 11th-grade group from the technical emphasis in healthcare. The school does not have a specific curriculum for its English courses which affects the pacing of the course and the overall linguistic competence of students. Looking for alternatives to tackle this situation, I came across Content Language and Integrated Learning. It is an approach that offers the possibility of teaching a language through specific content and content through language. Two interviews to the CT, student-teacher journal and a survey allowed me to find out the extent to which this approach improved English comprehension.